2019
DOI: 10.1155/2019/6894714
|View full text |Cite
|
Sign up to set email alerts
|

Anticorrosion Behaviour ofRhizophora mangleL. Bark-Extract on Concrete Steel-Rebar in Saline/Marine Simulating-Environment

Abstract: This paper investigates anticorrosion behaviour of the bark-extract from Rhizophora mangle L. on steel-rebar in concrete slabs in 3.5% NaCl medium of immersion (for simulating saline/marine environment). Corrosion-rate, corrosion-current, and corrosion-potential were measured from the NaCl-immersed steel-reinforced concrete cast with admixture of different plant-extract concentrations and from positive control concrete immersed in distilled water. Analyses indicate excellent mathematical-correlation between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 91 publications
(111 reference statements)
0
2
0
Order By: Relevance
“…Green corrosion inhibitors could be extracted even from bark of plants, as in the case of bark extract admixture from Rhizophora mangle L. extracted using methanol [57]. Different concentrations of the extract were tested as corrosion inhibitors for carbon steel rebars embedded in concrete immersed in a 3.5 wt.% solution of NaCl.…”
Section: Tests In Concretementioning
confidence: 99%
“…Green corrosion inhibitors could be extracted even from bark of plants, as in the case of bark extract admixture from Rhizophora mangle L. extracted using methanol [57]. Different concentrations of the extract were tested as corrosion inhibitors for carbon steel rebars embedded in concrete immersed in a 3.5 wt.% solution of NaCl.…”
Section: Tests In Concretementioning
confidence: 99%
“…Before weighing and recording the weight, the sample was allowed to dry. The corrosion rate was calculated using the formula as follows [14][15][16][17]:…”
Section: Impact Testmentioning
confidence: 99%
“…As a further matter, there is a growing appeal for developing different green-based corrosion inhibitors acquired from plant extracts in combating the corrosion of reinforced steel in concrete structures because of the less toxic and biodegradable nature of the extracts [11,[16][17][18][19][20]. Studies reported that the suitability of the N-, S-, and O-containing and π electron-rich leaves extracts of Phyllanthus muellerianus [18], Chamaerops humilis L. [20], and Olea europaea [21] acted as an effective anticorrosion agent for reinforcing steel in concrete.…”
Section: Introductionmentioning
confidence: 99%